The role of mirror neurons in observational motor learning: an integrative review - Angel Lago-Rodríguez; Binith Cheeran; Giacomo Koch; Tibor Hortobagy; Miguel Fernandez- (Asociación Española de Ciencias del Deporte, 2014)
Mirror neurons were discovered in the early 1990's in the premotor cortex of the rhesus macaque. These  special, visuo-motor neurons discharge action potentials when executing an action, as well as during the observation of the performance of a similar action. During an observational motor learning protocol, learners acquire new motor patterns based on the visual information presented by an execution model. In order to do so, learners have to transform the observed visual information into motor commands (visuo-motor transformation). Studies show that observational motor learning may improve action perception and motor execution. Moreover, action perception and action execution interact in a mutual and bi-directional fashion (visuo-motor and motor-visual interaction), suggesting that perception and action share common neural mechanisms. Mirror neurons have been proposed as the neurophysiological basis of the visuo-motor and motor-visual transformation processes, and may play a role in the perceptual and motor improvements induced by observational motor learning.